Respostas

2013-11-26T21:02:55-02:00
3x² -6x+0 =0 
delta = 36
6maisoumenos6 dividido por 6 
12/6 = x'=2 
0/6 = x"= 0 
2013-11-26T21:12:02-02:00
3x² - 6x - 3 = - 3
3x² - 6x - 3 + 3 = 0
3x² - 6x = 0
a = 3                b = - 6                  c = 0
∆ = b² - 4 . a . c 
∆ = (- 6)² - 4 . 3 . 0
∆ = 36 - 0
∆ = 36
x = - b ± √∆ 
      ¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
         2 . a
x = - (- 6) + √36 
       ¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
             2 . 3
x = 6 +
    ¨¨¨¨¨¨¨¨¨¨¨¨
         6
x' = 6 + 6  
         6
x' = 12 ÷ 6
x' = 2

x" = 6 - 6 
         2
x" = 0 
÷ 2
x" = 0
Resposta: {2, 0}